DAMPAK PERUBAHAN TARIF IMPOR KEDELAI TERHADAP KESEJAHTERAAN MASYARAKAT INDONESIA - Ryan Primasari; Suhatmini Hardyastuti; Jangkung Handoyo Mulyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2010)
In 1998-2004, Indonesia liberalized soybean trade on zero percent tariff rate, then reinstated tariff rate on 10 percent in 2005-2007 and removed It again in early 2008 due to price instability in world market. Because of Indonesian high import-dependency on soybean, the change of soybean import tariff is very important for farmer, consumer, and government. The objectives of this research are : 1) to analyze the effect of soybean import tariff change on domestic price, soybean quantitiy supplied, demanded, and imported; and (2) to analyze effects of soybean import tariff change on social welfare. Analyses used are partial equilibrium analysis, price, demand, and supply function and economic surplus indicator. Partial equilibrium analysis conclude that 10% tariff-cut scenario would increase soybean demanded and decrease soybean supplied in response to the decrease of both wholesaler and producer price. Thus, it would lead the increase of net welfare gain, but would squeeze the national soybean agriculture by the decrease of producer surplus and the increase of soybean import quantity. Meanwhile, the increase of tariff rat by 10% has the opposite results. It is suggested, therefore, that Indonesian government has to retain the import tariff to protect soybean producer and improve soybean production at the same time to pursue national food independency, especially for soybean.